Emotional Experience Predicts Social Adjustment Independent of Neurocognition and Social Cognition in Schizophrenia - Tso, Ivy F. (2010)
BACKGROUND: Emotion abnormalities are prominent features of schizophrenia. While the capacity for emotions is essential to social adaptation, little is known about the role of emotional experience in the social dysfunction observed in schizophrenia. OBJECTIVE: This study examined the contribution of emotional experience, neurocognition, and social cognition to functional outcome in schizophrenia. METHOD: Self-reported emotional experience (anhedonia, affect intensity, emotion frequency) was assessed in 33 stable schizophrenic/schizoaffective patients and 33 healthy controls. Symptoms, neurocognition, social cognition, and functional outcome were also assessed. RESULTS: Patients and controls exhibited good internal reliability on all self-report scales, except for negative affect intensity. Patients reported equally intense but less frequent positive emotions, more intense and frequent negative emotions, and more anhedonia. Results of hierarchical regression analyses showed that emotional experience accounted for significant amounts of variance of social adjustment independent of neurocognition and social cognition. CONCLUSION: These data show that emotional experience can be reliably assessed and is an important determinant of functional outcome in schizophrenia.